2019
DOI: 10.3390/su11164499
|View full text |Cite
|
Sign up to set email alerts
|

Furthering Internal Border Area Studies: An Analysis of Dysfunctions and Cooperation Mechanisms in the Water and River Management of Catalonia, Aragon and the Valencian Community (Spain)

Abstract: Cooperation between countries or regions that share a political border is one of the primary concerns of border studies. However, while cooperation between states is a well-established field based on international agreements, the cooperation between internal-state regions is not as well understood and requires more exhaustive study. Cooperation agreements between regions are frequently based on the shared and collaborative management of environmental resources such as river basins. This paper aimed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The present study is framed in the context of a broader research project, focused on the analysis of different types of problem and conflict that have been generated in recent times (especially over the last four decades) in the internal border area (IBA) between three Spanish Autonomous Communities: Aragon, Catalonia, and the Valencian Community. The results of this research have been reported in a number of studies conducted at different scales and focusing on different themes [68][69][70]. These previous studies, based on the conducting of focus groups with public stakeholders (mayors and town clerks) in the territory analyzed, conclude that, for a significant majority of the problems considered, it is essential that cooperation be promoted between the autonomous administrations.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The present study is framed in the context of a broader research project, focused on the analysis of different types of problem and conflict that have been generated in recent times (especially over the last four decades) in the internal border area (IBA) between three Spanish Autonomous Communities: Aragon, Catalonia, and the Valencian Community. The results of this research have been reported in a number of studies conducted at different scales and focusing on different themes [68][69][70]. These previous studies, based on the conducting of focus groups with public stakeholders (mayors and town clerks) in the territory analyzed, conclude that, for a significant majority of the problems considered, it is essential that cooperation be promoted between the autonomous administrations.…”
Section: Methodsmentioning
confidence: 90%
“…A questionnaire for the ARCAT-IBA public stakeholders (mayors and town clerks) was created with five main objectives: (i) to determine their perception of the deficiencies in UPS management as a result of the different regulations being operated in Aragon and Catalonia, respectively (Q1 in Table 1); (ii) to identify the existence of any formal or informal mechanisms of cooperation being employed by the Catalan and Aragonese administrations (Q2 and Q3 in Table 1); (iii) to appreciate their willingness to strengthen inter-municipal cooperation in the management of UPS, so that the citizens of ARCAT-IBA municipalities might access these services regardless of their origin (Q4 and Q5 in Table 1); (iv) to identify instruments to correct the deficiencies detected (Q6 in Table 1); and, finally, (v) to determine their perception of deficiencies at higher administrative levels (Q7 in Table 1). The questionnaire was answered in person between January and June 2017, following focus group sessions analyzed in previous studies devoted to water management [70]. Although there is evidence of general problems affecting local government in Spain and UPS management (e.g., budget deficits and shortages of administrative personnel), the questionnaire focuses on the specific problems attributable to their condition as border municipalities.…”
Section: Methodsmentioning
confidence: 99%